2017
DOI: 10.19080/aibm.2017.07.555714
|View full text |Cite
|
Sign up to set email alerts
|

Improved Albumin-Derived Per Fluorocarbon- Based Artificial Oxygen Carriers: In-vivo Evaluation of Biocompatibility

Abstract: Despite long lasting efforts, an artificial oxygen carrier displaying adequate gas solubility combined with a minimal risk of side effects is missing at present for clinical use, both in Europe and USA. To bypass this bottleneck, recently developed albumin-derived per fluorocarbonbased nanocapsules were further improved and tested in-vivo. Most importantly, this second nanocapsule generation reached a smaller size distribution that resulted in partially less side effects compared to the first capsule formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…We successfully synthesized nanoscaled PFOCs with a perfluorodecalin (PFD) core surrounded by a biocompatible albumin shell (capsules) 13 . Previous studies successfully describe the in vivo biocompatibility in a rat-top-load model and the functionality in an ex vivo isolated rat heart model 11,14,15 . Herein, we used a rat model of massive hemodilution, where we exchanged about 95% of the blood volume with either capsules in a plasma-like solution (treatment) or the plasma-like solution without capsules (control) and posthumously surveyed hypoxia sensitive organs such as the small intestine and kidney.…”
mentioning
confidence: 99%
“…We successfully synthesized nanoscaled PFOCs with a perfluorodecalin (PFD) core surrounded by a biocompatible albumin shell (capsules) 13 . Previous studies successfully describe the in vivo biocompatibility in a rat-top-load model and the functionality in an ex vivo isolated rat heart model 11,14,15 . Herein, we used a rat model of massive hemodilution, where we exchanged about 95% of the blood volume with either capsules in a plasma-like solution (treatment) or the plasma-like solution without capsules (control) and posthumously surveyed hypoxia sensitive organs such as the small intestine and kidney.…”
mentioning
confidence: 99%
“…Amphiphilic albumin as shell material encloses a core of PFD, thus avoiding the requirement of an additional emulsifier. In vitro tests have shown effective oxygen transport capacity of A-AOCs (Wrobeln et al 2017b), further supported by the proof of functionality in the Langendorff-heart-model (Wrobeln et al 2017c) and in vivo studies of the rat regarding toxicity and pharmacokinetics (Wrobeln et al 2017a). Intravenous application of A-AOCs was well tolerated in rats without change in systemic parameters and with stabile vascular perfusion.…”
Section: Main Textmentioning
confidence: 88%
“…Parameters of tissue injury showed no relevant deviations and the half-life of A-AOCs (158 min) was sufficient (Wrobeln et al 2017b). An in vivo proof-of-concept-study then demonstrated survival of rats after progressive exchange of 95% of blood with A-AOCs (Wrobeln et al 2017a).…”
Section: Main Textmentioning
confidence: 99%
“…It has been used in cell lines (in vitro) and animal models (in vivo) to evaluate the efficacy and safety of PFC (Table 7 ). A new development of A-AOC showed better biocompatibility and longer half-life circulation, thus resulting in good oxygen transportation in different animal models (Wrobeln et al 2017b ; Ferenz 2017 ). It was well-tolerated by intravenous administration and gave higher oxygen transport capacity in rats compared to Perftoran® (Wrobeln et al 2017a ).…”
Section: Aocs and Their Benefitsmentioning
confidence: 99%